Kepemimpinan Putra Mahkota Terhadap Runtuhnya Dinasti Abbasiyah - Safira, Mulia (CV RIFAINSTITUT, 2023)
The Abbasid dynasty adopted a system of appointing a caliph based on lineage, just like the Umayyah dynasty. This event as inversely proportional to what happened at the time of the prother Muhammad SAW, who appointed the caliph with deliberations among the Muslims. The appointment of a hereditary caliph wa one of the factors for the collapse of Islam during the Abbasid dynasty, due to the occurrance of bloody events and the everthrow of office when the crown prince was elected. As a result of this selfish attitude resulted in bloody event in the struggle for power and the occurrance of civil war so that it became a bad impact for the Abbasid dynasty